Two-dimensional Raman correlation spectroscopy reveals molecular structural changes during temperature-induced self-healing in polymers based on the Diels–Alder reaction1. Issue 35 (21st September 2015) - Geitner, R.; Kötteritzsch, J.; Siegmann, M.; Bocklitz, T. W.; Hager, M. D.; Schubert, U. S.; Gräfe, S.; Dietzek, B.; Schmitt, M.; Popp, J.
<x xml:space="preserve">Abstract</x> For the first time two-dimensional Raman correlation analysis has been used to study self-healing polymers based on the Diels–Alder reaction.